1990
DOI: 10.1007/bf01420191
|View full text |Cite
|
Sign up to set email alerts
|

Influence of surgery and antiepileptic drugs on seizures symptomatic of cerebral tumours

Abstract: One hundred and twenty-eight adult patients presenting with and operated on for supratentorial neoplasms were studied. Sixty-five had preoperative seizures and were treated with antiepileptic drugs (AEDs). Among the 63 patients without preoperative epileptic fits, 41 were given AEDs (either phenobarbital or phenytoin) as prophylactic treatment and 22 were not treated. The preoperative epilepsy course was considered with respect to tumour site and histological type. Early and late postoperative seizure occurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
101
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(104 citation statements)
references
References 16 publications
2
101
0
1
Order By: Relevance
“…Our data suggest that we could only rule out a risk reduction of more than 46% if patients took anticonvulsants prophylactically. However, when considered in conjunction with other randomized trials (or portions thereof 7,38,39 ), and a metaanalysis, 37 the results suggest prophylactic anticonvulsants are ineffective. The lower than expected seizure and survival rates we found in our patients suggested we needed to accrue ≥ 900 patients to have an adequately powered study; this was clearly not feasible or reasonable and we terminated the study.…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that we could only rule out a risk reduction of more than 46% if patients took anticonvulsants prophylactically. However, when considered in conjunction with other randomized trials (or portions thereof 7,38,39 ), and a metaanalysis, 37 the results suggest prophylactic anticonvulsants are ineffective. The lower than expected seizure and survival rates we found in our patients suggested we needed to accrue ≥ 900 patients to have an adequately powered study; this was clearly not feasible or reasonable and we terminated the study.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, only three immediate or early postoperative seizures were recorded in these patients compared with 13 seizures in a group of 185 control patients randomized to placebo, and the number of patients with seizures also was lower in the PHT group (two vs. nine in controls), even though these differences failed to reach statistical significance. A smaller trial in which 63 patients operated on for tumor were randomized to PHT, PB, or no treatment also suggested that treatment could protect against early-onset seizures, by the effect was not statistically significant (18). Although a statistically significant reduction in the risk of early postoperative seizures by PHT could be demonstrated by North et al (8) in a placebo-controlled trial in a total of 281 patients (including 34 with head injury), no protective effect could be demonstrated in the first week of treatment, and only seizures occurring between 7 and 72 days after surgery were reduced significantly by PHT.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors advise against prophylactic drug treatment (2,6,19,20), others suggest that PHT may be indicated for the immediate postoperative period (7,18,21,22). More remarkably, the practice of prescribing long-term AED prophylaxis remains widespread, either in all patients at large or in specific patient subgroups (23,24), despite lack of adequate evidence that postoperative and posttraumatic epilepsy can be prevented by treatment (4,6,9,14,25).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, no impairment of consciousness was witnessed in those treated compared to 18% of those untreated, suggesting that a putative subclinical epileptogenicity was averted. Postoperative complications (i.e., hemorrhage, worsening edema) raise the likelihood of seizures during the initial 48 hour period by over two-fold, including status epilepticus even in the presence of antiepileptic medical coverage [9]. Late postoperative seizures were found to occur in 34% of those patients who had presented preoperatively with seizure activity.…”
Section: Antiepileptic Medical Managementmentioning
confidence: 99%
“…In particular, epilepsy occurs in over 80% of patients with low-grade gliomas [7] and 30-60% of those with high-grade gliomas [8]. Factors which favour epileptogenesis in low-grade tumours appear related to slow growth kinetics coupled with cerebral location [9,10]. The relative risk for a cerebral tumour following a diagnosis of epilepsy approaches 20-fold overall compared with control and, when differentiated between malignant and benign tumours, it is about 26-fold and 10-fold, respectively [11].…”
Section: Introductionmentioning
confidence: 99%